Apoptosis of uninfected cells induced by HIV envelope glycoproteins - Ahr, Barbara (BioMed Central, 2004)
Apoptosis, or programmed cell death, is a key event in biologic homeostasis but is also involved in the pathogenesis of many human diseases including human immunodeficiency virus (HIV) infection. Although multiple mechanisms contribute to the gradual T cell decline that occurs in HIV-infected patients, programmed cell death of uninfected bystander T lymphocytes, including CD4+ and CD8+ T cells, is an important event leading to immunodeficiency. The HIV envelope glycoproteins (Env) play a crucial role in transducing this apoptotic signal after binding to its receptors, the CD4 molecule and a coreceptor, essentially CCR5 and CXCR4. Depending on Env presentation, the receptor involved and the complexity of target cell contact, apoptosis induction is related to death receptor and/or mitochondria-dependent pathways. This review summarizes current knowledge of Env-mediated cell death leading to T cell depletion and clinical complications and covers the sometimes conflicting studies that address the possible mechanisms of T cell death.